IDNLearn.com is the perfect place to get detailed and accurate answers to your questions. Join our community to receive prompt and reliable responses to your questions from knowledgeable professionals.

Sonya added two rational expressions, and then simplified her answer. The simplified answer was x + 1. What are the missing values in her original expression?

Sagot :

Answer:

[tex]a = 2[/tex] and [tex]b = 4[/tex]

Step-by-step explanation:

Given

The expression is:

[tex]\frac{x^2 + ax - 4}{x + 2} + \frac{x + b}{x + 2} = x + 1[/tex] --- missing from the question

Required

Find a and b

Take LCM

[tex]\frac{x^2 + ax - 4+x + b}{x + 2} = x + 1[/tex]

Cross Multiply

[tex]x^2 + ax - 4+x + b = (x+2)*(x + 1)[/tex]

Open brackets

[tex]x^2 + ax - 4+x + b = x^2+2x + x + 2[/tex]

[tex]x^2 + ax - 4+x + b = x^2+3x + 2[/tex]

Collect Like Terms

[tex]x^2 + ax +x + b- 4 = x^2+3x + 2[/tex]

[tex]x^2 + (a +1)x + b- 4 = x^2+3x + 2[/tex]

By comparing the coefficients:

[tex]a + 1 = 3[/tex]

[tex]a = 3 - 1[/tex]

[tex]a = 2[/tex]

[tex]b - 4 = 2[/tex]

[tex]b = 4[/tex]

Hence,

[tex]a = 2[/tex] and [tex]b = 4[/tex]

Answer:

a = 2

b = 6

Edg 2021